ON THE ISSUE OF PATRIOTISM AND UPBRINGING THROUGH CIVIC EDUCATION - G. Myagmarjav; D. Enkhchimeg (International Journal of Innovative Technologies in Social Science, 2024)
We consider the educational management methods aimed at developing patriotic citizens as respecting the roots and core culture of the Mongolian people. It is focused on cultivating a strong sense of valuing one’s country, developing individuals who dedicate their intellect, passion, talent, knowledge, and strength to the sustainable development and progress of their nation. This includes a desire for ambition, courage, perseverance, and behaviors that embody what it means to be a ’Mongolian.’ Furthermore, to enhance the guarantee of the country’s independence and ensure sustainable development, nationwide campaigns are being implemented with the goal of fostering patriotism and education through national programs such as ’Patriotic Mongolian’ and ’Fostering Patriotic Views Among Children and Youth. Education is not only knowledge, it is explained by the integrated concept of upbringing, development and morals. Moral education is included in civic education, and based on the development of patriotism, the importance of "New Era" education policy and the participation of the state and the people has been considered. Materials and Methodology: Sections related to the concept of national security, Mongolia’s Defense Law, Laws on Education, and the government’s agenda were compared. The management methods, possibilities, and future direction of the problem of cultivating patriotism and upbringing through civic education were clarified from its internal basis and reasons.